2007
DOI: 10.1007/s10577-006-1115-9
|View full text |Cite
|
Sign up to set email alerts
|

Genes flanking Xist in mouse and human are separated on the X chromosome in American marsupials

Abstract: X inactivation, the transcriptional silencing of one of the two X chromosomes in female mammals, achieves dosage compensation of X-linked genes relative to XY males. In eutherian mammals X inactivation is regulated by the X-inactive specific transcript (Xist), a cis-acting non-coding RNA that triggers silencing of the chromosome from which it is transcribed. Marsupial mammals also undergo X inactivation but the mechanism is relatively poorly understood. We set out to analyse the X chromosome in Monodelphis dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…Thus, spermatogenic events regulating transcriptional activity of the sex chromosomes are very well conserved in the marsupial and eutherian. This is in striking contrast to the absence of conservation in XIC elements that regulate XCI in the eutherian soma (39)(40)(41)(42). These data are consistent with a mechanism of im- printed XCI that would occur independent of XIST in the marsupial and make possible a mechanism that relies instead on inheritance of a silent X derived from the male germ line (5,25,(28)(29)(30).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, spermatogenic events regulating transcriptional activity of the sex chromosomes are very well conserved in the marsupial and eutherian. This is in striking contrast to the absence of conservation in XIC elements that regulate XCI in the eutherian soma (39)(40)(41)(42). These data are consistent with a mechanism of im- printed XCI that would occur independent of XIST in the marsupial and make possible a mechanism that relies instead on inheritance of a silent X derived from the male germ line (5,25,(28)(29)(30).…”
Section: Resultsmentioning
confidence: 57%
“…Eutherian XCI is regulated by the X-inactivation center (XIC/Xic), which contains the noncoding genes Xist (32)(33)(34), Tsix (35)(36)(37), and Xite (38). Repeated attempts to find the XIC orthologue in marsupials have failed and instead find that the syntenic region is rearranged (39)(40)(41). Interestingly, a recent report suggests that the ancestral XIST was vertebrate LNX3, a protein-coding gene with functions still extant but unrelated to dosage compensation in the marsupial (42).…”
mentioning
confidence: 99%
“…Although Xic clearly regulates imprinting in eutherians, XIC or an equivalent has yet to be identified in marsupials (11,12,22,55). The absence of a marsupial Xist suggests that an alternative means of silencing the X must occur in mammals.…”
mentioning
confidence: 99%
“…Physical mapping and bioinformatic analyses revealed that the region homologous to the X inactivation centre is disrupted by independent rearrangements in marsupials and monotremes (Hore et al 2007;Shevchenko et al 2007), and it was suggested that XIST evolved from a protein coding gene (Lnx3) in this region, whose loss of function coincided with pseudogenization of flanking genes (Duret et al 2006). These findings challenge a pivotal role in X inactivation for XIST and raise many fundamental questions about the mechanism and evolution of this important epigenetic system.…”
mentioning
confidence: 99%